Pendidikan Kecerdasan Sosial Emosional dalam Diskursus Pendidikan Islam: Studi Bibliometrik Pemetaan Literatur Internasional - Hamdi, Hamdi; Mahfuzh, Taufik Warman; Supriadi, Akhmad; Huda, Ali Anhar Syi’bul (Jurnal Pendidikan Agama Islam Al-Thariqah, 2025)
This study examines the lack of attention to social and emotional learning (SEL) education. The aim of this research is to analyze trends, sources, and themes of scientific publications regarding SEL in the period from 2015 to 2025, as well as to provide recommendations for future research. The method applied is quantitative bibliometrics, which involves an analysis of 200 publications from the Scopus database using tools such as Publish or Perish, VOSviewer, and Microsoft Word. The analysis results show that the topics of social and emotional learning (SEL) experienced an increase peaking in 2019-2020, but significantly declined until 2025. Emotional Intelligence (EI) emerged as a main theme, particularly in terms of its impact on individuals and social relationships. However, the integration of EI with social intelligence, digital literacy, and practical interventions is still very limited. The conclusion of this study shows that EI has not been fully explored, thus further development of more comprehensive, practical, and contextual studies is needed